Tenascin in meningioma: Expression is correlated with anaplasia, vascular endothelial growth factor expression, and peritumoral edema but not with tumor border shape - (:unkn) unknown (My University, 2002)
OBJECTIVE: Tenascin is an extracellular matrix glycoprotein that is expressed during embryogenesis, inflammation, angiogenesis, and carcinogenesis. The aim of this study was to investigate how tenascin expression relates to histological grade, angiogenesis, and radiological findings in meningiomas. METHODS: Twenty typical, 20 atypical, and 5 malignant meningiomas were studied retrospectively. Tenascin expression and vascular endothelial growth factor (VEGF) expression in the tumor tissue were investigated by immunohistochemistry. Tenascin messenger ribonucleic acid expression was also studied by comparative reverse transcriptase-polymerase chain reaction. Magnetic resonance images from each case were assessed for peritumoral edema and tumor border shape. RESULTS: The atypical and malignant meningiomas showed higher levels of tenascin expression than the typical meningiomas. The more sensitive messenger ribonucleic acid-based methods confirmed this finding. Tenascin expression was correlated with peritumoral edema and VEGF expression but not with tumor border shape. In the 13 tumors with marked tenascin expression, peritumoral edema was Grade 0 in one, Grade 1 in three, and Grade 2 in nine specimens. In the same 13 tumors, VEGF expression was Grade 1 in five and Grade 2 in eight specimens, and the findings for tumor border shape were Grade 0 in seven, Grade 1 in four, and Grade 2 in two specimens. CONCLUSION: In meningiomas, tenascin expression is correlated with anaplasia, tumor-associated edema, and VEGF expression but not with tumor border shape. This protein may play a role in the neoplastic and/or angiogenic processes in atypical and malignant meningiomas and may thus be a potential target for meningioma therapy.
Keywords: Angiogenesis; Extracellular matrix; Meningioma; Peritumoral edema; Tenascin